Optimasi Penjadwalan Kegiatan Pondok Pesantren Dengan Precedence Diagram Method (PDM) - Yaqin, M. Ainul; Fadhilah, Farah Rizky; Rohmawati, Linda; Umami, Lisa Aulia (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Islamic boarding school is a place for those who want to further explore the science of Islam. Not only a place to gain religious knowledge, Islamic boarding schools also have an education system that handles the scheduling system. The schedule is something that must be present in every activity in the Islamic boarding school. The activities at the Islamic boarding school are also quite numerous and crowded. In boarding schools, the problem faced is determining the schedule of Islamic boarding school activities so that the schedule of activities can be arranged optimally. In preparing the activity schedule, there are several things that must be considered, including the human resources involved, the facilities or facilities and infrastructure used, as well as the time taken during the activity. Of all Islamic boarding school activities in one year, it is necessary to have a calculation to find out how optimal the arrangement of the activity schedule is according to 52 boarding school standards. This study uses the Precedence Diagram Method (PDM) method by using a network diagram that can be used to complete the duration of the activities at the Islamic Boarding School conducted. The results of this study obtained an optimal schedule of activities with less time spent than the initial schedule arrangement that takes a total of 116 hours to carry out activities within one year. Using PDM project management can schedule Islamic boarding school activities so that activities can be completed on time.